KUALITAS PELAYANAN TOUR LEADER DI PT REZKI JASTY TOUR & TRAVEL PEKANBARU - Nana Riana; Syofia Achnes (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
The reseacrh aims to find out how the service quality of the tour leader in the PT.Rezki Jasty Tour & Travel Pekanbaru.This study used a descriptive quantitative method to examine problems in the lift. The samples in this study were 75 respondents, who were taken by using simpel random sampling. While data collection techniques in this study using observation, questioner, and literature. By using a Likert scale as a measure to determine the length of the short interval.From the results of research that’s been done, it looks that service quality of the tour leader in the PT.Rezki Jasty Tour & Travel Pekanbaru is good.Keywords : Service Quality, Tour Leader, Reliability, Responsiveness, Assurance, Emphaty, and Tangible.